A human embryonic stem cell-derived clonal progenitor cell line with chondrogenic potential and markers of craniofacial mesenchyme. (July 2012) - Sternberg, Hal; Murai, James T; Erickson, Isaac E; Funk, Walter D; Das, Shreyasi; Wang, Qian; Snyder, Evan; Chapman, Karen B; Vangsness, C Thomas; West, Michael D
Aims: We screened 100 diverse human embryonic stem-derived progenitor cell lines to identify novel lines with chondrogenic potential.Materials & methods: The 4D20.8 cell line was compared with mesenchymal stem cells and dental pulp stem cells by assessing osteochondral markers using immunohistochemical methods, gene expression microarrays, quantitative real-time PCR and in vivo repair of rat articular condyles.Results: 4D20.8 expressed the site-specific gene markers LHX8 and BARX1 and robustly upregulated chondrocyte markers upon differentiation. Differentiated 4D20.8 cells expressed relatively low levels of COL10A1 and lacked IHH and CD74 expression. Transplantation of 4D20.8 cells into experimentally induced defects in the femoral condyle of athymic rats resulted in cartilage and bone differentiation approximating that of the original tissue architecture. Relatively high COL2A1 and minimal COL10A1 expression occurred during differentiation in HyStem-C hydrogel with TGF-β3 and GDF-5.Conclusion: Human embryonic stem cell-derived embryonic progenitor cell lines may provide a novel means of generating purified site-specific osteochondral progenitor cell lines that are useful in research and therapy. Original submitted 6 March 2012; Revised submitted 5 April 2012; Published online 23 April 2012